2018
DOI: 10.1136/archdischild-2018-314769
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a new device for automated closed loop control of inspired oxygen concentration on fluctuations of arterial and different regional organ tissue oxygen saturations in preterm infants

Abstract: Closed-loop FiO using SPOC significantly increased time of arterial SpO within the intended range in VLBWI and decreased the need for manual adjustments when compared with the routine adjustment by staff members. StO was not significantly affected by the mode of oxygen control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 17 publications
4
24
1
Order By: Relevance
“…Recent targeting of higher saturations is associated with an increase in need for treatment for ROP [86], and in Sweden the effect of increased risk of ROP has negated the sensitivity of poor postnatal growth for prediction of ROP [87]. Servo-controlled oxygen algorithms are now sufficiently developed to maintain saturations within targeted range more of the time both with ventilated infants and those receiving non-invasive respiratory support, although no studies have been sufficiently powered to determine if there are any beneficial effects on outcome [88, 89]. …”
Section: Oxygen Supplementation Beyond Stabilisationmentioning
confidence: 99%
“…Recent targeting of higher saturations is associated with an increase in need for treatment for ROP [86], and in Sweden the effect of increased risk of ROP has negated the sensitivity of poor postnatal growth for prediction of ROP [87]. Servo-controlled oxygen algorithms are now sufficiently developed to maintain saturations within targeted range more of the time both with ventilated infants and those receiving non-invasive respiratory support, although no studies have been sufficiently powered to determine if there are any beneficial effects on outcome [88, 89]. …”
Section: Oxygen Supplementation Beyond Stabilisationmentioning
confidence: 99%
“…Sixteen single or multicentre clinical studies have been undertaken comparing closed loop automated oxygen control to manual oxygen control in neonates to determine whether automating FiO 2 control was associated with a greater target SpO 2 achievement. They consistently demonstrated that closed loop automated oxygen control maintained the patient within their target SpO 2 range a significantly greater proportion of the time than manual control . Closed loop automated oxygen control has been demonstrated to reduce hyperoxic episodes, in one study almost halving the frequency (9.3 to 4.7 episodes per 90 minutes) and the duration (19.3 s‐10.1 s) of hyperoxic episodes and in another study reducing the median percentage time spent with an SpO 2 > 95% from 41.9% to 19.3% ( P < .001) .…”
Section: Resultsmentioning
confidence: 94%
“…Multiple studies have found that automated oxygen control systems lead to a decrease in the number of manual interventions made by staff . Studies have reported that clinical staff needed to adjust the FiO 2 less than once per hour when there was automated control, compared with as many as 29 times per hour during manual control . A randomised study of one automated FiO 2 system found that the automated system made 7540 FiO 2 adjustments in a 12‐hour period, whereas staff made 80 adjustments over the same time period in the manual control group .…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate their system, they compared the time spent at the oxygenation target using the controller to a clinician-in-the-loop system. This metric was also used by others [38][39][40][41][42][43][44] and the automated system was as good or better than the manual procedure in all cases.…”
Section: Control Based On Gas Exchangementioning
confidence: 95%
“…A recent review of oxygenation control was published by Claure and Bancalari in 2013 [46]. The systems presented by Claure et al [41], Urschitz et al [42], and Gajdos et al [44] have been developed further and are now commercially available as AVEA-CLiO2 (CareFusion, Yorba Linda, CA, USA), CLAC (Löwenstein Medical GmbH & Co. KG, Bad Ems, Germany), and SPOC (Fritz Stephan GmbH, Gackenbach, Germany), respectively. Setpoint control is the dynamic response of the system to changes of the target.…”
Section: Control Based On Gas Exchangementioning
confidence: 99%